2019
DOI: 10.1155/2019/4080274
|View full text |Cite
|
Sign up to set email alerts
|

Blasting Impact Simulation Test and Fragmentation Distribution Characteristics in an Open‐Pit Mine

Abstract: Based on the split Hopkinson pressure bar (SHPB) test system, dynamic impact tests of coal specimens under different impact pressures were carried out to study the relationship between the impact load and the size of crushed lump coal. Based on the theory of stress wave attenuation, the relationship between the blasting impact load in a single-hole blasting area of a coal seam and the load applied in an impact failure test of a coal specimen in the laboratory was established. According to the characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It can not only realize simple loads with high strain rate, but also form dynamic loads composed of various loads, such as active and passive confinement pressure [14]. SHPB experimental device can be applied to the field of blasting [15]. The experimental method is to indirectly promote the stress-strain relationship of sample material by measuring the strain on the impact prop.…”
Section: Laboratory Impact Test Of Coal Samplesmentioning
confidence: 99%
“…It can not only realize simple loads with high strain rate, but also form dynamic loads composed of various loads, such as active and passive confinement pressure [14]. SHPB experimental device can be applied to the field of blasting [15]. The experimental method is to indirectly promote the stress-strain relationship of sample material by measuring the strain on the impact prop.…”
Section: Laboratory Impact Test Of Coal Samplesmentioning
confidence: 99%
“…Zhang et al [ 24 ] found that the double phase fluid of gas will break great particles into granulum while it is ejected from the outburst port at high velocity, and the crushing outcome rises with the increase of methane pressure. Based on the split Hopkinson pressure bar measurement system, Ding et al [ 25 ] studied dynamic crushing tests on coals under different impacts, and studied the relationship between crushing load and particle extent of fragmented coal. Luo et al [ 26 ] evaluated the impact power of coal with distinct particle extents in outburst.…”
Section: Introductionmentioning
confidence: 99%
“…et al [10] used (LS-DYNA) to perform blasting of a coke rock bench Numerical simulations, from rock stress perspective, stress clouds and stress curves from numerical simulations, concluded that the root cause of the high dust production from blasting operations was the excessive fragmentation of the coke rocks after the blast wave, and the excessive blast energy was converted into kinetic energy to drive the dust to escape. Song, Y. q. et al [11,12] conducted dynamic compression tests on lignite with different impact rates, and the results showed that the increase in strain rate had a significant hardening effect on the dynamic mechanical parameters of the rock samples, and the stress-strain curve had an obvious "double-peak" feature; meanwhile, macroscopic cracks in the rock appeared at the first stress peak and disappeared after further compression until interlaminar fracture occurred. Zhang Y.J et al [13,14] used the finite element program LS-DYNA to establish a double millisecond hole model for desktop blasting, and through analysis of the numerical simulation results, obtained that peak particle velocity (PPV) and energy decay occurred near the blasting source, which provided a basic theory for the protection of buildings near the blasting source.…”
Section: Introductionmentioning
confidence: 99%